Fundamentals of European Civil Law - Angelo, A H (Victoria University of Wellington Law Review, 1997)
This article is a book review of Martin Vranken Fundamentals of European Civil Law (Federation Press, Sydney, 1997) 290 + xiv pages including Appendix, Bibliography and Index. Soft cover, NZ$45. Angelo states that the book is very tightly and clearly presented, providing a good introductory text for several purposes including the central topics of comparative law, a basic introduction to the law of contract, tort labour law and commercial company law in the French and German systems, as well as within the context of the European Union. Angelo concludes that the book provides a reasoned and correct view of the impact of the European Union on aspects of the private law of the member states.